Cloud security and privacy : an enterprise perspective on risks and compliance - Mather, Tim.; Kumaraswamy, Subra; Latif, Shahed (Farnham : O'Reilly, 2009)
Cloud computing has emerged as a popular way for corporations to save money that would otherwise go into their IT infrastructure. This book Addresses issues that affect any organization preparing to use cloud computing as an option. It covers the steps you need to take to ensure your web applications are secure and your data is safe.
Introduction -- What is cloud computing? -- Infrastructure security -- Data security and storage -- Identity and access management -- Security management in the cloud -- Privacy -- Audit and compliance -- Examples of cloud service providers -- Security-as-a-[cloud] service -- The impact of cloud computing on the role of corporate IT -- Conclusion, and the future of the cloud.
Includes bibliographical references and index.
1
Keywords: Cloud computing -- Security measures